A study of the stress-strain state of tibial osteosynthesis models after high tibial valgus osteotomy - Korzh, Mykola; Barysh, Oleksandr; Buznytsky, Ruslan; Yaresko, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The stress-strained state in a finite element model of C III/C VII vertebromotor segments was comparatively analysed in conditions of modelling of different variants of bisegmental anterior interbody fusion of C IV/C VI with help of vertical cylindrical mesh implants, including two new techniques developed. It was revealed that the configuration of the implants and peculiarities of their placement in the interbody space played an important part in the distribution and change of values of the stress-strained state for bodies of the vertebrae, which were stabilized.